2020
DOI: 10.1080/21691401.2019.1709851
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of hyperoside against hydrogen peroxide-induced dysfunction and oxidative stress in osteoblastic MC3T3-E1 cells

Abstract: Oxidative stress can induce apoptosis and decrease activities of osteoblasts. Hyperoside (HYP) is a potent antioxidant derived from Chinese herb. This study aims to evaluate the protective effects provided by HYP to osteoblastic MC3T3-E1 cells. MC3T3-E1 cells were pre-treated with HYP for 24 h before being treated with 0.3 mM hydrogen peroxide (H 2 O 2) for 24 h. Cell viability, flow cytometric analysis and mRNA expression of alkaline phosphatase (ALP), collagen I (COL-I) and osteocalcin (OCN) in MC3T3-E1 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…It has been reported to alleviate the effects of oxidative stress damage, to varying degrees, in the treatment of inflammatory apoptosis. 12,13 H 2 O 2 acts as an inducer of oxidative stress in vitro and can induce apoptosis in many different cell types, but H 2 O 2 can be inhibited by antioxidants. 14 Therefore, this study explored the role of hyperoside as an antioxidant and studied its protective mechanism in H 2 O 2 -treated PC12 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported to alleviate the effects of oxidative stress damage, to varying degrees, in the treatment of inflammatory apoptosis. 12,13 H 2 O 2 acts as an inducer of oxidative stress in vitro and can induce apoptosis in many different cell types, but H 2 O 2 can be inhibited by antioxidants. 14 Therefore, this study explored the role of hyperoside as an antioxidant and studied its protective mechanism in H 2 O 2 -treated PC12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…11 It has also been shown that hyperoside can reduce H 2 O 2 -induced osteoblast MC3T3-E1 phosphorylation Jun terminal kinase (JNK) and lower P38 levels by inhibiting mitogen-activated protein kinase (MAPK) signaling; it reduces H 2 O 2 -induced cell apoptosis and apoptosis-related proteins. 12 However, there are only a few studies that have explored the protective mechanism of hyperoside in alleviating the oxidative stress injury of neurons. In this study, PC12 rat pheochromocytoma cells, a sympathetic nervous system tumor-cell line widely used to study neuronal injury-related models and highly similar to dopaminergic neurons in structure and function, were selected to establish an H 2 O 2 -induced oxidative-injury model.…”
mentioning
confidence: 99%
“…In recent years, HP has also been studied in anti-osteoporosis. HP can protect MC3T3-E1 from oxidative stress via inhibiting the MAPK signaling pathway and oxidative damage of the cells [20], reduce the apoptosis and autophagy rate of MC3T3-E1. In addition, HP also has a good anti-osteoporosis performance in OVX mice through NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with quercetin and arbutin ameliorates bone loss by reducing bone resorption [25,31,32,[66][67][68] through the suppression of osteoclasts activity and the stimulation of osteoblast activity [69][70][71][72][73]. Hyperoside protects osteoblasts from oxidative stress [74,75], while astragalin stimulates differentiation of osteoblasts [76]. Additionally, quinic acid promotes osteoblasts differentiation through activation of the Wnt/β-catenin pathway, while caftaric acid modulates RunX2 and RANKL/OPG signalling pathways [77].…”
Section: Discussionmentioning
confidence: 99%